2018
DOI: 10.1136/bmj.k4771
|View full text |Cite
|
Sign up to set email alerts
|

Business not as usual: how multisectoral collaboration can promote transformative change for health and sustainable development

Abstract: Shyama Kuruvilla and colleagues present findings across 12 country case studies of multisectoral collaboration, showing how diverse sectors intentionally shape new ways of collaborating and learning, using “business not as usual” strategies to transform situations and achieve shared goals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 27 publications
(49 reference statements)
1
76
0
2
Order By: Relevance
“…The recommendations that resulted from Task 5.3 are in line with the literature [29,30,32,[36][37][38]. Corbin et al [36] suggests nine core elements that constitute positive partnership processes.…”
Section: Discussionmentioning
confidence: 58%
“…The recommendations that resulted from Task 5.3 are in line with the literature [29,30,32,[36][37][38]. Corbin et al [36] suggests nine core elements that constitute positive partnership processes.…”
Section: Discussionmentioning
confidence: 58%
“…4b: n=18) included in the data extraction. investing in collaborative relationships; and agreeing on criteria for success (20). Similar recommendations can be found in reviews throughout the literature, many of which also draw substantially from case studies (5)(6)(7)(8)10,11,13,(21)(22)(23)(24)(25)(26).…”
Section: Figure 4: Distribution Of Research Methods On Msc By Topicalmentioning
confidence: 74%
“…From this study, we found three components of health governance and leadership to be important (Table 1) [1]: establishing child survival as a national priority [2]; involving multi-sectoral stakeholders and collaborations to participate in MNCH planning and implementation; and [3] creating and maintaining accountability through a 'monitor-review-act' approach. Without this overarching guidance, individual MNCH interventions remain fragmented and under-resourced [17][18][19][20]. Although some countries were able to effectively implement the monitor-review-act approach, greater investment in accurate, responsive, and integrated monitoring and evaluation systems will be needed to assess progress towards the more complicated and ambitious SDGs [8,[21][22][23][24].…”
Section: A Summary Of Key Findingsmentioning
confidence: 99%